Uma voz através das grades: testemunho, cárcere e contexto em Memórias de um sobrevivente e Às cegas, de Luiz Alberto Mendes - Ferreira, Patrini Viero (2019)
The two titles chosen as the corpus of analysis for this study are part of a literary niche still recently disseminated in the Brazilian scenario: the literature de cárcere. Memórias de um sobrevivente (2001) and Às cegas (2005), by Luiz Alberto Mendes, narrate the trajectory of the protagonist throughout his childhood, youth and adult life. The objective of this work, besides trying to construct a panorama of the historical period in which the narrative occurs, both in the political and social sense, is the search for an approximation of the selected corpus to the literature of testimony and to the literature de cárcere itself, identifying and recognizing throughout the fragments extracted from the books properties and particularities that can refer to the characteristics intrinsic to these literary tendencies. Therefore, the methodology adopted is analytical, that is, excerpts will be selected from both works that may contribute to the identification of the issues determined in the objectives of this study. As a theoretical basis for this analysis, names such as Aulus Mandagará Martins, Marcio Seligmann-Silva, Hugo Achugar, Jaime Ginzburg, Michel Foucault and Maria Rita Palmeira are mobilized here. This study intends to develop in the reader not only a new way of seeing the social reality faced by the subject in a situation of imprisonment, but also to give him the possibility of carrying out a somewhat empathic reading of this context of production, taking into account the individualities of the representations of subjects in these reports.